Bartter Syndrome With Normal Aldosterone Level and Acute Pancreatitis: An Unusual Presentation - Noor Ayaz; Matti Ullah; Waqar Ahmad; Farhan Ullah; Ikram Ullah Khan; Fahad Naim; Awais Naeem; Fatima Sajjad; Kamil Ahmad Kamil (Clinical Case Reports, 2026)
ABSTRACT Bartter syndrome is a rare autosomal recessive renal tubulopathy, which classically presents with hypokalemic metabolic alkalosis, hyperreninemia, and hyperaldosteronism. We report an atypical presentation in a 16‐year‐old male who was diagnosed following an initial manifestation of acute pancreatitis. Key biochemical findings included profound hypokalemia (1.4 mEq/L), metabolic alkalosis, hyperreninemia (218.5 uIU/mL), and hypercalciuria, yet with a normal serum aldosterone level, which is a notable deviation from the classic biochemical profile. The acute pancreatitis was attributed to severe hypokalemia‐induced pancreatic ductal dysfunction. This case underscores that a normal aldosterone level does not exclude Bartter syndrome and emphasizes the importance of considering this possibility in patients with hypokalemic alkalosis and renal salt‐wasting. Furthermore, it highlights severe hypokalemia as a potential, life‐threatening precipitant of acute pancreatitis, warranting prompt investigation in affected patients presenting with acute abdominal pain.